Human amniotic fluid stem cells can improve cerebral vascular remodelling and neurological function after focal cerebral ischaemia in diabetic rats. Issue 21 (7th October 2021) - Liang, Ching‐Chung; Shaw, Steven W.; Huang, Yung‐Hsin; Lee, Tsong‐Hai
Abstract: Diabetes causes vascular injury and carries a high risk of ischaemic stroke. Human amniotic fluid stem cells ( hAFSCs) can enhance cerebral vascular remodelling and have the potential to improve neurological function after stroke in diabetic rats. Five groups of female rats were examined: (1) normal control, (2) type 1 diabetic (T1DM) rats induced by streptozotocin injection (DM), (3) non‐DM rats receiving 60‐minute middle cerebral artery occlusion (MCAO), (4) T1DM rats receiving 60‐minute MCAO (DM + MCAO) and (5) T1DM rats receiving 60‐minute MCAO and injection with 5 × 10 6 hAFSCs at 3 h after MCAO (DM + MCAO + hAFSCs). Neurological function was examined before, and at 1, 7, 14, 21 and 28 days, and cerebral infarction volume and haemorrhage, cerebral vascular density, angiogenesis and inflammatory were examined at 7 and 28 days after MCAO. hAFSCs treatment caused a significant improvement of neurological dysfunction, infarction volume, blood‐brain barrier leakage, cerebral arterial density, vascular density and angiogenesis and a reduction of brain haemorrhage and inflammation compared with non‐treatment. Our results showed that the effect of hAFSCs treatment against focal cerebral ischaemia may act through the recovery of vascular remodelling and angiogenesis and the reduction of inflammation in ischaemic brain.